PENGARUH KUALITAS PELAYANAN DAN PELAKSANAAN PROMOSI TERHADAP MINAT BELI ULANG JASA KAMAR PADA AYOLA FIRST POINT HOTEL KOTA PEKANBARU - Wida Wulandari; Lie Othman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine the effect of service quality and promotion implementation on the interest in repurchasing room services at Ayola First Point Hotel Pekanbaru partially and simultaneously. In this study, the method used was a quantitative approach and used analytical tools, namely SPSS version 23. The respondents in this study were 100 people who used the Ayola First Point Hotel room service. Furthermore, the results obtained are that there is a positive and significant influence between Service Quality (X1) and Repurchase Interest (Y), Promotion Implementation (X2) has a positive and significant effect on Repurchase Interest (Y), and Service Quality (X1) and Implementation Promotion (X2) has a positive and significant effect on Repurchase Interest (Y) Room Service At Ayola First Point Hotel Pekanbaru City. Keywords: Service Quality, Promotion Implementation, and Repurchase Interest